2017
DOI: 10.1002/anie.201709197
|View full text |Cite
|
Sign up to set email alerts
|

The MOF+ Technique: A Significant Synergic Effect Enables High Performance Chromate Removal

Abstract: A significant synergic effect between a metal–organic framework (MOF) and Fe2SO4, the so‐called MOF+ technique, is exploited for the first time to remove toxic chromate from aqueous solutions. The results show that relative to the pristine MOF samples (no detectable chromate removal), the MOF+ method enables super performance, giving a 796 Cr mg g−1 adsorption capacity. The value is almost eight‐fold higher than the best value of established MOF adsorbents, and the highest value of all reported porous adsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 66 publications
1
66
1
Order By: Relevance
“…Recently, we found that MOF + technique could be a good alternative to solve this problem (Figure ). Relative to the pristine MOF samples of USTA‐74 that gives no adsorption toward Cr VI , the samples with the presence of FeSO 4 affords ultrahigh Cr VI removal up to 796 Cr mg g −1 .…”
Section: Applying Mof+ Technique For Reduction and Remove Of Crvimentioning
confidence: 84%
“…Recently, we found that MOF + technique could be a good alternative to solve this problem (Figure ). Relative to the pristine MOF samples of USTA‐74 that gives no adsorption toward Cr VI , the samples with the presence of FeSO 4 affords ultrahigh Cr VI removal up to 796 Cr mg g −1 .…”
Section: Applying Mof+ Technique For Reduction and Remove Of Crvimentioning
confidence: 84%
“…For example, some metal-organic frameworks have been used for Cr(VI) adsorption, but generally show slow adsorption kinetics and limited capacities 3032 . A more recent study found that Cr(VI) adsorption to a metal-organic framework could be dramatically improved by adding exogenous Fe(II) 33 . This result implies that, similar to the case with iron oxides, the presence of Fe(II) can enhance reductive adsorption of Cr(VI).…”
Section: Resultsmentioning
confidence: 99%
“…And partial hydrogenation of acetylene into ethylene over catalyst 10 or solvent extraction of cracked olefins 11 are also involved with the purification of ethylene from acetylene. Adsorptive separation by porous materials is an alternative technology, especially, some metal-organic frameworks (MOFs) [12][13][14][15][16][17][18][19][20][21] with high volume, designable pore characteristics, and countless structural possibilities, can be employed into the gas separation processes, the adsorption selectivity and capacity are higher than the results of conventional adsorbents [22][23][24] such as zeolites and carbon-based, especially the adsorption and separation for C 2 H 6 /C 2 H 4 8,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
mentioning
confidence: 99%